Differences in caregivers' psychological distress and associated factors by care recipients' gender and kinship. (1st December 2016) - Iwata, Noboru; Horiguchi, Kazuko
Abstract : Objectives: In this study, we examined the level of psychological distress of Japanese caregivers according to various combinations of the gender of care recipients and the kinship of caregivers (spouse, son, daughter, or daughter-in-law). Furthermore, we explored the associated factors that could exacerbate or alleviate psychological distress. Methods: We utilized a cross-sectional descriptive design and implemented a self-administered questionnaire survey with a two-stage stratified sample of community-dwelling caregivers of frail elderly persons throughout Japan. We surveyed 1279 caregiving families, and 1020 questionnaires were completed by primary caregivers (response rate: 79.8%), with 945 respondents providing data on the Japanese version of the Kessler 6 psychological distress scale (K6). Results: Caregivers' K6 scores varied significantly by care recipients' gender and their relationship with the caregiver. K6 scores were significantly higher among daughters-in-law caring for fathers-in-law than among daughters-in-law caring for mothers-in-law, wives caring for husbands, or daughters or sons caring for mothers. 'Negative influence of caregiving' and 'anxious about continuing caregiving' were factors that commonly exacerbated caregivers' psychological distress. Further analyses involving interactions indicated that the effects of 'anxious about continuing caregiving' and 'personal growth through caregiving' on the psychological distress of daughters-in-law varied by care recipients' gender as did the effects of an alleviating factor, 'keeping their own pace', on daughters. Conclusions: Psychological distress levels among family caregivers, as well as exacerbating and alleviating factors, varied depending on the gender and kinship of care recipients.